2135. Costs vs. Earnings in Colon Surgery and Coronary Artery Bypass Grafting Under a Prospective Payment System: Sufficient Financial Incentives to Reduce Surgical Site Infections?. (26th November 2018) - Juchler, Fabrice; Roth, Jan; Schweiger, Alexander; Dangel, Marc; Gugliotta, Massimo; Battegay, Manuel; Eckstein, Friedrich; Kettelhack, Christoph; Abshagen, Christian; Hug, Balthasar L; Boyce, John M; Widmer, Andreas F
Abstract: Background: Little is known about actual hospital earnings in patients with and without surgical site infections (SSI) under a prospective payment system. To exemplify respective financial incentives for hospitals to prevent SSI, we aimed to compare hospital costs and earnings in colon surgery and coronary artery bypass grafting (CABG) patients, with and without SSI. Methods: Based on a national and validated SSI surveillance cohort, we performed a nested financial analysis at a participating tertiary care center in Switzerland. Consecutive patients with colon operations and CABGs from January 2015 through December 2016; and from January 2015 through October 2016, respectively, were included. Co-primary outcome measures were actual hospital costs and earnings under a prospective payment system (SwissDRG), stratified by SSI status. Ascertainment of SSI status was performed as part of a standardized follow-up protocol at 1 month and one year after surgery. Results: In colon surgery ( n = 229), the median costs were 68, 796 (interquartile range [IQR], 39, 600–95, 217) with SSI and 26, 556 (IQR, 18, 282–54, 230) without SSI (unadjusted P < 0.001; adjusted P = 0.001). In CABGs ( n = 433), the median costs were 117, 170 (IQR, 57, 329–201, 953) with SSI and 48, 855 (IQR, 40, 053–67, 860) without SSI (unadjusted P < 0.001; adjusted P < 0.001). In colon surgery, the median earnings were −10, 738 (IQR, −33, 275 to −3, 492) with SSI and −2, 223 (IQR, −13, 009 to 4, 917) without SSI (unadjusted P = 0.001; adjusted P = 0.038). In CABG, the median earnings were −25, 050 (IQR, −54, 060 to −10, 882) with SSI and −2, 485 (IQR, −11, 597 to 3, 375) without SSI (unadjusted P < 0.001; adjusted P < 0.001). Conclusion: Hospital costs and earnings for two common surgical interventions varied substantially under a prospective payment system: SSIs after colon and CABG operations resulted on average in higher costs and lower earnings. A prospective payment system may add a strong financial incentive to reduce SSI rates after colon and CABG operations. Disclosures: All authors: No reported disclosures.